Subjective aspects of aging Medellín’s social support net and senior aticens’ autonomy - Cardona Arango, Doris; Estrada Restrepo, Alejandro; Agudelo García, Héctor Byron (Investigación y Educación en Enfermería, 2008)
Aiming to identify and to analyse the availability and autonomy of the social support nets serving the Medellín senior citizens population, in 2002, a 637 elders survey was carried through a randomized selection process between the 6498 old-age telephone subscribers inscribed in the 2002 Quality-of-life Survey. Family is the best informal net provider of support for 90% of the senior citizens. It is a vital factor providing well-being and satisfaction to them. Formal nets like social organization are cited by 28% of them. The senior citizens perception about their skills and abilities to perform daily routines, was assessed in its relative importance in order to enhace personal autonomy and self-esteem. Accordingly it was found that 96% of them were able to perform the basic daily physical activities, 90% the basic social activities and 80% the instrumental activities. Key words: Seniors, Social Support, Aging poblation, Autonomy, Old age.